Suicide in the Qur'an: A Causal-Thematic Analysis of Ayat al-Intihar - Zulfan Nabrisah; Ahmad Fajar Shodik (Jurnal Al-Hikmah, 2025)
Data from the Indonesian National Police (Polri) indicate that suicide ranks fourth among cases classified as public order disturbances in the country, with economic hardship cited as one of the primary causes. This phenomenon underscores the idea that worldly struggles can lead individuals to neglect the eternal nature of the afterlife. A particularly compelling issue arises from the fact that the majority of Indonesia’s population is Muslim; as such, the Qur’an should serve as a guide for life. The Qur’an strongly discourages despair, highlighting the vastness of God’s mercy, as emphasized in Surah Al-A’raf (7:56). This study focuses on two key questions: How does the Qur’an describe verses related to suicide (ayat al-intihar), and how can a causal analysis be derived from those verses? The objective is to identify Qur’anic verses with themes related to suicide and then conduct a causality-based analysis to understand the underlying causes and propose solutions. The research uses a qualitative approach through a library study, employing the thematic interpretation (tafsir maudh?‘?) method for verse collection and applying causality theory for analysis. The findings reveal that the Qur’anic foundation for the prohibition of suicide is primarily found in Surah An-Nisa’ (4:29) and Surah Al-Isra’ (17:33). The various factors that lead to suicide ultimately stem from a sense of despair caused by weakened faith in Allah, the Supreme Owner of life. Therefore, the most appropriate solution for individuals facing hardship is to remain patient and place their trust in Allah, as no problem exists in this world without a corresponding solution.